(untitled) (Plant Tissue Culture and Biotechnology, 2015)
Micropropagated plants of Curculigo orchioides Gaertn. through five different modes of regeneration were evaluated for their genetic stability and major flavanoids content that contribute to medicinal properties of the rhizome. Leaf explants that produced callus and bulbils have produced plantlets at a higher frequency. However, direct regeneration of plants from leaf tissues without intervening callus produced a low frequency of plantlets. Explants of rhizome produced healthy plantlets directly from the terminal part of the explant. Plantlets regenerated through five different modes of regeneration did not show any morphological variation. The duration of regeneration was varying from 60 to 145 days depending upon the type of the explant. Analysis of genomic DNA among the plantlets regenerated through five different modes of micropropagation revealed about 66% polymorphism. Major flavanoids such as rutin, ferulic acid, caffeic acid, quercitrin that contributed to medicinal properties of the rhizomes differed quantitatively among the plantlets regenerated through different pathways. Present study suggests that plantlets regenerated directly from the rhizome as well as from the leaf tips of in vitro grown plants are stable genetically and phytochemically. Plant Tissue Cult. & Biotech. 24(2): 173-189, 2014 (December)